Understanding the dynamics of study motivation: An in-depth analysis of teachers' perceptions in primary schools - Lena Boström; Göran Bostedt; Ingela Stenberg (Journal of Pedagogical Research, 2023)
Research has shown students' study motivation is complex and demanding. It also asserts that teachers' perceptions and attitudes are decisive, complex, and demanding because they need to make many choices about planning and handling lessons and review their fundamental beliefs about study motivation. We aimed to describe teachers' perceptions of students' study motivation. We collected the data from nine focus-group interviews with 26 Swedish teachers in five primary schools. Through reflexive thematic analysis, the following six themes of perceptions emerged: emotions, teachers, teaching, learning environment, family and friends, and health and well-being. Although many teachers assumed students have more intrinsic than extrinsic motivation, they described more extrinsic motivation factors. Changing factors of importance for study motivation are primarily background factors, things needed to feel and function in everyday life, such as good health, friends, and functioning relationships. The study's results make an important contribution to understanding teachers as a starting point for understanding their didactic choices and how these choices can affect students, as well as how teaching could be changed to correspond more closely to students' needs and conditions.